Characteristics of obstetric fistula women repaired at Kisii Gynocare Fistula Centre - Omboga, John (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the characteristics of obstetric fistula women repaired at the Kisii Gynocare fistula centre. Specifically the study sought to determine the ages of women and age at which they developed obstetric fistula, level of education, whether in gainful employment or not, marital status of fistula women and whether they had good social family support and number of children born to a fistula survivor. The study also focused on each women’s labor experiences taking into account whether delivery occurred in a hospital or not, duration of labor, mode of delivery and whether skilled health workers attended to the fistula survivor or not. Methods: The study employed both qualitative and quantitative study methods. A survey sample (n=157) was used and in which interviewer administered questionnaire; both open ended and closed ended were used. Qualitative data was obtained by participant observation (face to face in-depth interviews) and key informant interviews. Both purposive and snowball sampling methods were employed to recruit study subjects. The setting was Kisii Gynocare Fistula Centre in Kisii County, about 420 km south west from the Kenyan capital Nairobi. Results: The majority of the women (n=98,62.4%) were in the reproductive age 15-40 years. 68 (43.3%) had attained secondary level education 34(21.6%) dropped at primary and 27(17.2%) had attained tertiary education level. 17(10.8%) were in some formal employment and the rest were peasant farmers and others engaged in small scale business enterprises. 72(45.8%) were in marriage, 40(25.5%) divorced or widowed and 45(28.7%) were single. Among those presented with RVFs majority had many children (more than 2) while of those who had VVFs (n=66) had no child (the child died at birth) or had 1-2 children. Many of those with VVFs (n=49) reported experiencing leakage of urine within a week of difficult delivery and in their early first or second pregnancy at 15-24 years while those with RVFs were evenly spread throughout the reproductive years (15-40 years). Among the VVF group (n=66), 47(71.2%) reported they labored at home. 19(28.8%) went to hospital/health centre at advanced labor. All of them reported being in labor for between 1-3 days. Among the RVF group, most (n=78) reported presenting to the hospital in time and that they were attended by ‘students’ during delivery while others reported by the time a midwife came the babies were already out. On mode of delivery, 14(21.2%) of VVF women reported leaking urine after undergoing a c-section. This was after many hours of unrelieved long labors. All women in the RVF group reported they developed tears and RVF after a difficult vaginal delivery. Majority of women (n=119) reported that they did not attend ANC clinics at all throughout their pregnancy and 13.4% (n=21) reported attending ANC once or twice. The remainder 10.l8% (n=17) attended all the WHO recommended focused ANC attendance. Conclusions: 8 in 10 women with OF developed fistula at their first pregnancy at a very young age. Majority of these women did not have adequate formal education, many being school drop-outs; 9 in 10 women labored at home and only transferred to hospitals late. A large number, 7 in 10, were not in gainful employment. A major social impact of OF include ostracization and stigmatization by the community and divorce from the spouse. Women suffering from OF also lose jobs, don’t participate in income generating activities and are resigned to perennial poverty. They lose self esteem and many of them become depressed.